PATRON-CLIENT RELATIONSHIP PADA MASYARAKAT MADURA - Mohammad Hefni (Institut Agama Islam Negeri Madura)
Abstrac This article traces patron-client relationship of Madurese both from socio-historical point of view and its contemporary progress. As an imbalance social-exchange relationship, in terms of patron-client relationship, second side (client) much highly depends upon the first side (patron). This had been experienced in Madurese social history during the native governmental period of time. The government was classified into two major classes; ruler class (patron) and farmer class (client). The former is fully in authority to take control either economic or politic potencies, however, the later transacts labors to the first side. Both side is connected by a bribe (upeti) systems—percaton, apanage and daleman. In current progress this relationship becomes more acquaintance, it covers economic and politic relationship. The success of Trunojoyo, the king of Sumenep's inherit, against the Mataram domination had been supported by Madurese people that had previously tightened to the system. Today, patron-client relationship in Madura is reflected in the relationship between the head of village, as the owner of percaton, and the staff as well as people, as the percaton manager. The other is well-described in the relationship of ship owner and pandega (fisher) in fishing. Once the relationship is set up, it directs to diadik relation, a two in one relation which is more personal and long lasting one. Kata-kata kunci Patron-klien, percaton, apanage, panembahan, rakyat, daleman, kepala desa, juragan, pandega, dan diadik.